Comparison on Characterization of Cinderella from â€œCinderellaâ€ Grimmâ€™s Fairy Tale (1812) and â€œCinderellaâ€ Grimmâ€™s Fairy Tale Edited by Edna Henry Lee Turpin (1903) - Andika Pratama (STKIP AGAMA HINDU SINGARAJA, 2023)
This study aims to describe and the characterization of Cinderella from Cinderella Grimm’s Fairy Tale, written by the Grimm Brothers version (1812), and Cinderella Grimm’s Fairy Tale, edited by Edna Henry Lee Turpin (1903) version in the perspective of the psychoanalytic study. The method that is used to explore the elements of both fairy tales is textual analysis. The subject of this research is two novels entitled Cinderella Grimm’s Fairy Tale (1812) and Cinderella Grimm’s Fairy Tale, edited by Edna Henry Lee Turpin (1903). The object of the study is the characterization of the main character from both fairy tales, Cinderella. The analysis is done by detailing the characterization of Cinderella from the point of view of the Id, Ego, and Superego, which is reflected through her behavior in certain occurrences. The result of the study is that the characterization of Cinderella in both versions has similarities, namely pious, kind, weak, beautiful, patient, mysterious, diligent, modest, naïve, and dependent. In addition, there are three differences in the traits which only occurred in the Grimm’s Fairy Tale (1812), including more dependent, egoistic, and reckless.